The relationship between the choice of a strategy of behavior in conflict and character accentuations (on the example of teenagers) (The Journal of Psychology and Sociology, 2021)
The article theoretically justifies and practically proves that the presence of a certain type of charac- ter accentuation in a teenager determines the choice of a strategy for behavior in conflict. Accentuations are considered as disharmony of character development, hypertrophied expression of individual per- sonality traits. In this regard, it is assumed that the effectiveness of preventive actions on the adolescent will increase based on the consideration of multiple character traits, including pathologically developed ones.The article presents the results of an experimental study aimed at identifying the prevailing types of character accentuations in adolescents; the study of their behavior strategies in conflict situations and an assessment of the nature of the relationship between the strategies of behavior in the conflict and the types of character accentuations. The sample consisted of 100 people. To assess the accentuations of character and strategies of behavior in the conflict, the MPDO – Modified questionnaire for identify- ing the types of character accentuations in adolescents, the questionnaire of Kenneth Thomas (Kenneth Thomas) “Determination of the way of conflict” was used. The study found that adolescents with ac- centuated traits require a different attitude from others, which will contribute to more effective conflict resolution. Based on the findings of the study, it is substantiated that taking into account character ac- centuations increases the possibilities of preventive work with conflict behavior of adolescents.Key words: personal characteristics, character, accentuations, disharmony, hypertrophied expres- sion, interpersonal interaction, conflict, conflict situation, behavior strategies.